Consumer Shopping Behavior towards Retail Stores In Coimbatore City - Vidhya, Dr. P.; Jegadeeshwaran, Dr. M. (International Journal of Scientific Research and Management (IJSRM), 2017)
India is ranked as the most attractive emerging retail market in the world and has earned itself theunflattering label of a “nation of shop keepers”. As consumer shopping behavior and preferences differfrom country to country, the retailers have to adopt the consumer shopping mentality. They have to studyconsumer culture, business practices, and industry dynamics based on their attention towards retail stores.Analyzing in order to meet the changing demand of consumers, a huge revamping exercise is on. Thisstudy is an attempt to prove that attention and interest of the consumers towards retail products changetheir buying behavior towards retail stores.